2021
DOI: 10.3389/fphar.2021.658811
|View full text |Cite
|
Sign up to set email alerts
|

Yi-Qi-Jian-Pi Formula Suppresses RIPK1/RIPK3-Complex-Dependent Necroptosis of Hepatocytes Through ROS Signaling and Attenuates Liver Injury in Vivo and in Vitro

Abstract: Acute-on-chronic liver failure (ACLF) is described as a characteristic of acute jaundice and coagulation dysfunction. Effective treatments for ACLF are unavailable and hence are urgently required. We aimed to define the effect of Yi-Qi-Jian-Pi Formula (YQJPF) on liver injury and further examine the molecular mechanisms. In this study, we established CCl4-, LPS-, and d-galactosamine (D-Gal)-induced ACLF rat models in vivo and LPS- and D-Gal-induced hepatocyte injury models in vitro. We found that YQJPF signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“… 63 The latest research indicated that Yi‐Qi‐Jian‐Pi Formula (YQJPF) decreased hepatocyte necroptosis in the acute‐on‐chronic liver failure (ACLF) model, consisting of inhibiting the expression of RIPK1 and RIPK3 and blocking the formation of necrosome. 64 Meanwhile, YQJPF reduced the level of ROS in hepatocytes, which had the same effect as selective RIPK1 inhibitor Nec‐1, suggesting that YQJPF inhibited necroptosis by reducing ROS signalling.…”
Section: Crosstalk Between Necroptosis and Other Ald‐associated Patho...mentioning
confidence: 89%
“… 63 The latest research indicated that Yi‐Qi‐Jian‐Pi Formula (YQJPF) decreased hepatocyte necroptosis in the acute‐on‐chronic liver failure (ACLF) model, consisting of inhibiting the expression of RIPK1 and RIPK3 and blocking the formation of necrosome. 64 Meanwhile, YQJPF reduced the level of ROS in hepatocytes, which had the same effect as selective RIPK1 inhibitor Nec‐1, suggesting that YQJPF inhibited necroptosis by reducing ROS signalling.…”
Section: Crosstalk Between Necroptosis and Other Ald‐associated Patho...mentioning
confidence: 89%
“…RIPK1, RIPK3 and MLKL are all targets of intervention against necroptosis-mediated inflammation and pathology ( Dannappel et al, 2014 ; Mulay et al, 2016 ; Martens et al, 2020 ; Liu et al, 2022 ). To date, various inhibitors targeting RIPKs have been developed ( Martens et al, 2020 ; Wang et al, 2021 ) and have been shown to protect against the progression of various kidney diseases ( Mulay et al, 2016 ; Liu et al, 2018 ; Wang et al, 2019 ; Liu et al, 2022 ). We previously reported that two RIPK1 inhibitors, Cpd-71 and wogonin, attenuated cisplatin-induced nephropathy and were superior to the classical RIPK1 inhibitor Nec-1.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the CCl 4 +LPS/D−GalN-induced ACLF mouse model has also been used to test the potential therapeutic effects of drugs on ACLF [ 39 ]. We replicated murine models of ACLF and ALF with mortality by LPS+D−GalN and CCl 4 , as previously described [ 36 , 40 ]. Compared with ALF mice, latent cirrhotic ACLF mice showed a partially differentiated phenotype, including more serious liver function damage (higher ALT and AST), delayed time to death, and different histological morphology.…”
Section: Discussionmentioning
confidence: 99%